2021
DOI: 10.1111/xen.12684
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing attitudes toward xenotransplantation clinical trials: A report of focus group studies

Abstract: Background Clinical trials of xenotransplantation (XTx, ie, cross‐species transplantation, specifically the transplantation of genetically engineered pig organs into human recipients) are due to start within a few years. Methods Five focus groups were conducted in April‐May 2019, among local religious leaders (N = 10), organ procurement staff/administrators (N = 5), patients and parents of patients who may need an organ transplant or are transplant recipients (N = 9), and local businesspersons in the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…The opinions of patients, health care professionals, and members of the public need to be sought. A number of surveys and focus groups have been organized by Paris and his colleagues during the past three years, which indicate that the public is largely supportive of xenotransplantation [80] , [81] , [82] , [83] , [84] , [85] , [86] . The influence of religious beliefs has also been explored [ 87 , 88 ].…”
Section: Public Opinionmentioning
confidence: 99%
“…The opinions of patients, health care professionals, and members of the public need to be sought. A number of surveys and focus groups have been organized by Paris and his colleagues during the past three years, which indicate that the public is largely supportive of xenotransplantation [80] , [81] , [82] , [83] , [84] , [85] , [86] . The influence of religious beliefs has also been explored [ 87 , 88 ].…”
Section: Public Opinionmentioning
confidence: 99%
“…Our interdisciplinary group has conducted multiple research surveys and focus groups to elicit the public's perception of pediatric cardiac and adult kidney xenotransplantation. [3][4][5] We have consulted numerous stakeholders, including religious leaders, organ procurement staff/administrators, healthcare providers who care for possible future candidates, patients themselves, parents of children who may need an organ or are transplant recipients, and local businesspersons. [3][4][5] In summary, these studies found little or no religious, ethical, or social concerns among these stakeholders, with considerable support for xenotransplantation given results are comparable to allotransplantation (which, of course, is not yet known).…”
mentioning
confidence: 99%
“…[3][4][5] We have consulted numerous stakeholders, including religious leaders, organ procurement staff/administrators, healthcare providers who care for possible future candidates, patients themselves, parents of children who may need an organ or are transplant recipients, and local businesspersons. [3][4][5] In summary, these studies found little or no religious, ethical, or social concerns among these stakeholders, with considerable support for xenotransplantation given results are comparable to allotransplantation (which, of course, is not yet known). There was also support for its use to bridge patients until a deceased human donor organ could be obtained, which is our suggested therapy for infants.…”
mentioning
confidence: 99%
“…Basic problems of immune response have not been fully answered 22–24 . Patient selection is completely unclear and it appears, that there is no distinct patient population that could even remotely and temporarily benefit from cardiac xenotransplantation 25,26 . Fundamental ethical questions have been addressed, but only within the xenotransplant community 23 .…”
mentioning
confidence: 99%